Perkawinan Siri Sebab Tidak Memiliki Akta Perceraian dari Perkawinan Sebelumnya (Studi Kasus di Desa Sedayulawas Kecamatan Brondong Kabupaten Lamongan) - Khoiriyah, Nadya; Nafik, Moh.; Rizal, Moch. Choirul (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The magnitude of the practice of unregistered marriages that occurred in Sedayulawas Village is the main point the problem in this research is that the factors are very diverse, ranging from pregnancy outside the marriage, economy, desire for polygamy, avoiding adultery, and divorce are not recorded. Then the factor that becomes the focus of this research is unregistered divorce (not before the Court) with the highest number of perpetrators, namely ten people who have an impact on the occurrence of a second marriage in a series, because there is one of the administrative requirements which cannot be fulfilled is the divorce certificate. The interesting thing about the serial marriage, which is carried out by the wife, which if it is considered in the positive legal status that applies in Indonesia, she is still married to her first husband. This type of research is classified as an empirical legal research type with a static socio-legal or legal sociology. The data analysis technique used in empirical legal research is to take a systematic and factual picture. The results showed that the practice of unregistered divorces that occurred in Sedayulawas Village, Brondong District, is caused by several things, such as the economy, lack of understanding of the importance of recording divorce, and distance Courts far from the village. The practice of unregistered divorce is carried out very diverse ranging from vows of divorce verbally and in front of the village mudin (not before the Court) whose position does not have permanent legal force or is not recognized by the state. Because the implementation of divorce must be in accordance with the rules applied both in Undang-Undang Perkawinan Nomor 1 Tahun 1974 and Kompilasi Hukum Islam, if it is done outside of these rules then the divorce is not valid though has complied with religious rules.